Open Architecture and its Discontents - Jorge Mejía Hernández; Esin Komez Daglioglu (Footprint)
The qualities that characterise open works of art have become prevalent in mainstream architecture theory.  Trying to elucidate why openness appears to mean so many different things and at the same time remains an ethereal concept, it seems worthwhile to reflect on potential justifications for its use. While the notion can be effectively and persuasively used to discuss the ethics that should govern our profession, beyond that axiological role its meagre explanatory power suggests that new directions in open architecture might require that we recognise its theoretical shortcomings and start looking for new and better ways to explain exactly what we’re talking about when we talk about the architecture of our time.